Auxiliary methods for percutaneous dilatational tracheotomy (Annals of Medical Research, 2021)
Aim: Patient with long-term mechanic ventilation in the Intensive care unit can be used as an adjunct to the Light styles and Fiber optic bronchoscope as a guide in percutaneous dilatation tracheotomy. In our study, we planned to investigate the effects of Light styles and Fiber optic bronchoscope on perioperative complications in percutaneous dilatation tracheotomy.Material and Methods: The study was conducted by scanning digital and written file records of 52 patients who underwent percutaneous dilatation tracheotomy between 2016 and 2018. Patients were evaluated in 3 groups using Light styles, Fiber optic bronchoscope and no additional methods.Results: In the study; percutaneous dilatation tracheotomy were performed to 52 patients who were followed up at the Intensive care unit. Mean Percutaneous dilatation tracheotomy opening day was 17.03±4.18 days, operation time was 21.23±8.45 min, 69.2% was successful in the first attempt in all groups. There were 21 patients using Light styles, 12 using Fiber optic bronchoscope and 19 with no additional methods. In 26 patients (74.3%) the use of Light styles or Fiber optic bronchoscope was facilitated. In the Light styles group endotracheal tube puncture was less common (p=0.044). More venous hemorrhage was seen in longer periods of procedure (p0.001), and more hypotension was observed in the longer Percutaneous dilatation tracheotomy administration time in all groups (p=0.012).Conclusion: The use of Light styles and Fiber optic bronchoscope can be safely used in percutaneous dilatation tracheotomy. Keywords: Lighted stile; Fiber optic bronchoscope; percutaneous dilatation tracheotomy.
Keywords: Lighted stile; Fiber optic bronchoscope; percutaneous dilatation tracheotomy.